Engrenagem Inovativa: análise e detalhamento do Modelo de Sistema Regional de Inovação do Sudoeste do Paraná - Ribeiro, Hugo Alexandre Souza (2017)
The classic innovation system consider university, firm and government as key elements of the innovation process and the social, economic and environmental sustainability of municipalities, regions and countries. However, relationships between these three actors do not always occur in a simultaneous and coordinated way, so that bilateral relationships between government and university, between academia and firm, and between government and firm are more common. In this context, based on a constructivist and qualitative approach, through an action research, this study presents, analyzes and details the model of innovation system of the Southwest region of Paraná, called Innovative Gear, which has a fourth element as a facilitator of the innovation process. The organization was the Instituto de Desenvolvimento Tecnológico, de Pesquisa e Inovação do Sudoeste do Paraná (IDETEP), a private not-for-profit entity whose function is to connect universities, companies and government and stimulate cooperative innovation in the Southwest Territory. Finally, a framework was defined for essential elements of an innovation system, composed of culture and values, institutions and people, leadership, processes and tools, and results, which could inspire other territories to replicate or adapt the model of innovation, according to their needs, allowing further studies on the subject to be developed in order to perfect the Innovative Gear